(untitled) (Geographical Journal of Nepal, 2019)
Nepalese people have experienced climate variability for a long time and the mitigation and adaptation responses they have made to reduce the effect of climate variability are not new phenomena for Nepal. However, mainstreaming climate change issues into sectoral policies from the government can be seen as recent activities in Nepal. Nepal has contributed negligible amount of emissions of Greenhouse Gases (GHGs) of global greenhouse gas, it is the fourth most vulnerable country in the world. In this context, this paper aims to review climate change adaptation policies in terms of sectoral integration. This paper has adopted text-mining method for information retrieval and knowledge mining and followed step-by-step approach to undertake review of policies. It concludes that National Adaptation Programme of Action (NAPA) in 2010 can be a milestone in sectoral adaptation of climate change issue largely because it has provided the national framework for sectoral adaptation to climate change. However, NAPA ignores the importance of structural and institutional reforms needed for mainstreaming climate change adaptation into sectoral agencies. Climate change Policy, 2011, Local Adaptation Plan of Action (LAPA) 2011, Constitution of Nepal, 2015, Local Government Operation Act (LGOA) 2017, Disaster Risk Reduction and Management Act, 2017 and National REDD+ Strategy, 2018 are other prominent legislative and policy frameworks that have significant contribution in sectoral integration of climate change adaptation issues. However, lack of climate change act in order to implement fully these policies into practice for its implementation can be a major obstacle to achieve the goal. In this context, strong legislative foundation with effective institutional mechanism among different sectors will be very crucial to capture the spirit of new Federal Constitution of Nepal.